2018
DOI: 10.1001/jamapediatrics.2018.1273
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physical Activity With Income, Race/Ethnicity, and Sex Among Adolescents and Young Adults in the United States

Abstract: IMPORTANCE Physical activity in youth is associated with adult health. Understanding the prevalence and factors of moderate to vigorous physical activity among adolescents and young adults will guide public health and policy efforts. OBJECTIVES To describe the current patterns of physical activity and duration among adolescents and young adults and to identify the direction and magnitude of associations between physical activity and income, race/ethnicity, and sex. DESIGN, SETTING, AND PARTICIPANTS This cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
170
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(199 citation statements)
references
References 33 publications
23
170
5
1
Order By: Relevance
“…Despite these limitations, this study was one of the few studies of MVPA in adolescents with type 1 diabetes guided by behavioral considerations and measuring changes in behavioral processes, and the only one to utilize a group approach including not only parents but also peers. Also, in previous studies, diverse samples of adolescents including sociodemographic groups at elevated risk of physical inactivity and overweight (low income, female gender, ethnic/racial minority) within the type 1 diabetes and general adolescent population have not been as well represented in the study samples as they were in the present study. Adolescents in homes facing economic challenges often live in disadvantaged neighborhoods (higher concentration of poverty, greater number of abandoned homes) leading to more limited opportunities for engagement in MVPA (eg, family activities, free play, and organized sports).…”
Section: Discussionmentioning
confidence: 64%
“…Despite these limitations, this study was one of the few studies of MVPA in adolescents with type 1 diabetes guided by behavioral considerations and measuring changes in behavioral processes, and the only one to utilize a group approach including not only parents but also peers. Also, in previous studies, diverse samples of adolescents including sociodemographic groups at elevated risk of physical inactivity and overweight (low income, female gender, ethnic/racial minority) within the type 1 diabetes and general adolescent population have not been as well represented in the study samples as they were in the present study. Adolescents in homes facing economic challenges often live in disadvantaged neighborhoods (higher concentration of poverty, greater number of abandoned homes) leading to more limited opportunities for engagement in MVPA (eg, family activities, free play, and organized sports).…”
Section: Discussionmentioning
confidence: 64%
“…One potential explanation for this observation is the lack of physical activity opportunities for adolescents from some ethnic/racial minority groups and communities of lower SES. Analyses of NHAHES 2007-2016 data showed that adolescents from low-income families participated in less physical activity than more affluent adolescents [51]. This association may be the result of reduced access to parks, playgrounds, and exercise facilities, which is more prevalent in less advantaged communities [52]; a problem that is even more prevalent in communities where the population is predominantly of an ethnic/racial minority group [53].…”
Section: Socioecological Influencesmentioning
confidence: 99%
“…An adapted version of the Global Physical Activity Questionnaire (GPAQ), developed by the WHO [19], was administered directly to 12-15 year-olds at the Mobile Examination Center (MEC), and during inhome interviews to 16-17 year-olds [20]. The GPAQ captures aerobic PA in three domains: recreational, active transportation, and work (e.g.…”
Section: National Health and Nutrition Examination Survey Global Physmentioning
confidence: 99%